"Somebody Who Was on My Side": A Qualitative Examination of Youth Initiated Mentoring. (May 2016) - Spencer, Renée; Tugenberg, Toni; Ocean, Mia; Schwartz, Sarah E. O.; Rhodes, Jean E.
Youth initiated mentoring (YIM) is an innovative approach to mentoring being implemented by the National Guard Youth ChalleNGe Program in which youth identify and select their mentors. There is great interest in this approach; however, there has been little study of YIM or its implementation in ChalleNGe. Retrospective in-depth qualitative interviews with former ChalleNGe participants ( n = 30) were conducted to gain a descriptive understanding of the mentor selection process, the role these relationships played in participants' experiences of the ChalleNGe program and in their lives more generally, and the nature and strength of these connections. Findings indicate that youth were able to successfully enlist the participation of mentors and YIM yielded enduring and emotionally supportive relationships. That the adults came from within their communities was viewed by these participants as having expedited the development of feelings of trust and contributed to the relevancy and meaningfulness of the guidance and advice offered.